Proposing a Neurotropic Etiology for Acute Posterior Multifocal Placoid Pigment Epitheliopathy and Relentless Placoid Chorioretinitis - Steptoe, Paul J.; Pearce, Ian; Beare, Nicholas A.V.; Sreekantam, Sreekanth; Mohammed, Bashar R.; Barry, Robert J.; Steeples, Laura R.; Denniston, Alastair K.; Murray, Philip I. (Frontiers in Ophthalmology, 2022)
Purpose To reassess the underlying pathophysiology of acute posterior multifocal placoid pigment epitheliopathy (APMPPE) and relentless placoid chorioretinitis (RPC) through comparison with the non-inoculated eye of the von Szily animal model of neurotropic viral retinal infection. Methods Narrative review. Results Literature reports of isolated neurotropic viral entities and rising serological viral titers in APMPPE after presentation support a potential direct infective etiology. In general, viral transport along axons results in mitochondrial stasis and disruption of axoplasmic flow. Clinical manifestations of axoplasmic flow disruption in APMPPE/RPC may signify the passage of virus along the neuronal pathway. From a case series of 11 patients, we demonstrate a timely, spatial, and proportional association of optic disc swelling with APMPPE lesion occurrence. Signs within the inner retina appear to precede outer retinal lesions; and acute areas of outer nuclear layer (ONL) hyperreflectivity appear to be the result of coalescence of multiple hyperreflective foci resembling axonal spheroids (which occur as a consequence of axoplasmic disruption) and follow the Henle fiber layer neurons. Underlying areas of retinal pigment epithelium (RPE) hyper-autofluorescence follow ONL hyperreflectivity and may signify localized infection. Areas of apparent choriocapillaris hypoperfusion mirror areas of RPE/Bruch’s membrane separation and appear secondary to tractional forces above. Increases in choroidal thickness with lesion occurrence and focal areas of choriocapillaris hypoperfusion are observed in both APMPPE/RPC and the von Szily model. Conclusions The neurotrophic infection model provides significant advantages over the existing primary choriocapillaris ischemia hypothesis to account for the range of imaging signs observed in APMPPE and RPC.